Evaluation of serum cortisol concentration and neutrophil to lymphocyte ratio before and after rectal palpation in a swamp buffalo cows (Bubalusbubaliscarabanensis) - Cierra, Weiwei (2017)
Rectal palpation is one of the veterinary procedures that is used to diagnose pregnancy in buffalo cows. However, this procedure might be painful and stressful to the animal. Stress is one of the important factors that need to be considered when assessing the welfare of the animal. The objective of this study is to evaluate stress response to rectal palpation by comparing serum cortisol concentration and neutrophil to lymphocyte ratio before and after rectal palpation in a buffalo cows. Blood was collected from the coccygeal vein before and directly after rectal palpation from 3 non-pregnant and 12 pregnant swamp buffalo cows aged between five to eight years old and weighing 300 to 400 kg. The serum cortisol concentration and neutrophil to lymphocyte ratio was determined using radioimmunoassay and differential count respectively to evaluate stress response to this procedure. The result revealed that there is significant increase in the serum cortisol concentration following a rectal palpation in pregnant and non-pregnant buffalo cows. However, there is no significant different between pregnant and non-pregnant buffalo cow in terms of responsiveness to rectal palpation. There is also no significant increase in neutrophil to lymphocyte ratio in both groups following a rectal palpation. Thus, this study show that rectal palpation in buffalo cows causes stress and the pregnancy status does not seem to influence the response to rectal palpation.